2014
DOI: 10.1136/bcr-2014-206369
|View full text |Cite
|
Sign up to set email alerts
|

Pseudozymaspp catheter-associated blood stream infection, an emerging pathogen and brief literature review

Abstract: Pseudozyma spp are amorphic yeasts. They are commonly plant pathogens, but rarely cause invasive fungal disease in humans. Only three cases of central venous catheter (CVC)-associated blood stream infections due to this organism have been reported in the literature. Main underlying risk factors for Pseudozyma spp infection are bowel surgery, CVC and total parenteral nutrition. We present a rare case of Pseudozyma spp catheter-associated blood stream infection that was successfully treated with antifungal thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…We retrospectively reviewed the global literature to identify the possible risk factors, clinical presentation, and optimal treatment strategies for Pseudozyma infection; in addition to the present case, 14 case reports were found (Table 1). 3,[7][8][9][10][11][12][13][14][15] Since 2014 when previous literature review was reported by Prakash et al [8], there were seven additional cases including our case. Therefore, we present a updated literature review with some modifications and adding recent cases.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…We retrospectively reviewed the global literature to identify the possible risk factors, clinical presentation, and optimal treatment strategies for Pseudozyma infection; in addition to the present case, 14 case reports were found (Table 1). 3,[7][8][9][10][11][12][13][14][15] Since 2014 when previous literature review was reported by Prakash et al [8], there were seven additional cases including our case. Therefore, we present a updated literature review with some modifications and adding recent cases.…”
Section: Discussionmentioning
confidence: 95%
“…seemed to have susceptibility to amphotericin B only. 13 In all reported cases, Pseudozyma spp. were resistant to echinocandins and flucytosine.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The plant pathogen Ustilago (the agent of corn smut) and the closely related genus Pseudozyma are ubiquitous in the environment and are commonly regarded as laboratory contaminants. However, these organisms can be transmitted by the airborne route and have occasionally caused fungemia and central venous catheter infections in humans (5,7,(10)(11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%